2013
DOI: 10.5830/cvja-2012-071
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of ischaemic heart disease in sub-Saharan Africa : review article

Abstract: BackgroundThe epidemiology of ischaemic heart disease (IHD) in sub-Saharan Africa (SSA) remains largely enigmatic. Major obstacles to our understanding of the condition include lack of reliable health statistics, particularly cause-specific mortality data, inadequate diagnostic capabilities, shortage of physicians and cardiologists, and misguided opinions.MethodsThis review of the epidemiology of ischaemic heart disease in sub-Saharan Africa involved a systematic bibliographic MEDLINE search of published data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 48 publications
1
68
0
Order By: Relevance
“…These factors notwithstanding, this study is one of the first in a rural community in SSA employing specific investigations for markers of atherosclerosis. THESUS-HF demonstrated that IHD was the most common cause of HF in urban Kenya (14), and other studies from the region support the notion of an increasing burden of IHD and risk factors thereof (12,50). These findings underscore the need to develop more accessible tools to diagnose IHD and for clinicians and policy makers to consider varied causes of HF in urban and rural settings.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…These factors notwithstanding, this study is one of the first in a rural community in SSA employing specific investigations for markers of atherosclerosis. THESUS-HF demonstrated that IHD was the most common cause of HF in urban Kenya (14), and other studies from the region support the notion of an increasing burden of IHD and risk factors thereof (12,50). These findings underscore the need to develop more accessible tools to diagnose IHD and for clinicians and policy makers to consider varied causes of HF in urban and rural settings.…”
Section: Discussionmentioning
confidence: 86%
“…To determine the extent to which atherosclerosis and ischemia contributed to HF, we used a combination of widely available, non-invasive techniques. We chose this approach based on limitations in access to a broad range of investigative tools and the “erroneously reinforced beliefs that IHD only affects the wealthy and the elderly” in SSA (12). The ABI, ECG, and echocardiogram have a modest to strong correlation to significant coronary artery disease or prior myocardial infarction (41,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…79 The WHO estimated that in 2005, IHD caused approximately 261,000 deaths in the African region, and current projections suggest that this number will be nearly 600,000 by 2030. It is estimated that agestandardized mortality rates for IHD will rise by 27% in African men and 25% in women by 2015, and by 70 and 74%, respectively by 2030 80 (Figure 4). The increase in IHD in Sub-Saharan Africa since the 1980s is presumably due to the increasing prevalence among African populations of the classical risk factors for CAD, including hypertension, smoking, diabetes, abdominal obesity and dyslipidemia.…”
Section: Communicable Diseasesmentioning
confidence: 99%
“…(1) According to the World Health Organisation (WHO), CVD is the leading cause of death globally accounting for an estimated 31% of all deaths worldwide. (2) Cardiovascular disease also poses a threat to the African continent, with several studies showing the prominence of a variety of cardiovascular afflictions in the African context, including heart failure and systolic dysfunction, (3) ischaemic heart disease (IHD), (4) hypertension and hypertensive heart disease (5) with associated heart failure. (6) Available data from the Medical Research Council of South Africa suggests that the predominance and treatment of common heart conditions in the population such as heart failure, cardiac hypertrophy and diseases of the valves and heart muscle are to a large extent, poorly managed.…”
Section: Introductionmentioning
confidence: 99%